2008
DOI: 10.1136/oem.2008.038901
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of chromosome translocations in airline pilots with long-term flying experience

Abstract: Background Chromosome translocations are an established biomarker of cumulative exposure to external ionising radiation. Airline pilots are exposed to cosmic ionising radiation, but few flight crew studies have examined translocations in relation to flight experience. Methods We determined the frequency of translocations in the peripheral blood lymphocytes of 83 airline pilots and 50 comparison subjects (mean age 47 and 46 years, respectively). Translocations were scored in an average of 1039 cell equivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 42 publications
2
34
0
3
Order By: Relevance
“…In addition, a recent survey of the exposure due to CRs demonstrated that none exceeded the recommended level of 6 mSv/y and the majority of aircrew received around 3 mSv/y (Bennett et al 2013a(Bennett et al , 2013b. However, according to several studies discovering chromosome aberrations in aircrew members, the topic deserves further investigations (Bolzan et al 2008;Yong et al 2009) as well as additional verification (Wolf et al 1999). Therefore, the development of new models as well as the improvement and validation of existing models for dose assessment, specifically during GLEs, is of a big importance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent survey of the exposure due to CRs demonstrated that none exceeded the recommended level of 6 mSv/y and the majority of aircrew received around 3 mSv/y (Bennett et al 2013a(Bennett et al , 2013b. However, according to several studies discovering chromosome aberrations in aircrew members, the topic deserves further investigations (Bolzan et al 2008;Yong et al 2009) as well as additional verification (Wolf et al 1999). Therefore, the development of new models as well as the improvement and validation of existing models for dose assessment, specifically during GLEs, is of a big importance.…”
Section: Discussionmentioning
confidence: 99%
“…For a NIOSH study of chromosome aberrations among commercial airline pilots and a comparison group of university faculty, the adjusted translocation frequency was significantly associated with flight years (P 5 0.01) with rate ratios of 1.06 [95% confidence interval (CI) 1.01-1.11] and 1.81 (95% CI 1.16-2.82) for a 1-and 10-year incremental increase in flight years, respectively (Yong et al, 2009).…”
mentioning
confidence: 99%
“…All the regression models were adjusted for flight years (quartiles: , 13·2, 13·2 -17·4, 17·5 -23·2 or $ 23·3) as well as for known confounders (22) : age at blood draw (#40, 41 -45, 46-50 or . 50 years), cumulative red bone marrow X-ray dose score (,0·5, 0·5-1·9 or $ 2·0), as calculated by Yong et al (22) , and military flying (yes or no).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…50 years), cumulative red bone marrow X-ray dose score (,0·5, 0·5-1·9 or $ 2·0), as calculated by Yong et al (22) , and military flying (yes or no). Additional adjustments were made for the following lifestyle factors: pack-years of cigarette smoking, alcohol intake, months of vigorous recreational activity and BMI (kg/m 2 ) as continuous variables.…”
Section: Statistical Analysesmentioning
confidence: 99%